Macrophage-mediated tumor-targeted delivery of engineered Salmonella typhimurium VNP20009 in anti-PD1 therapy against melanoma - Leyang Wu; Lin Li; Shufeng Li; Lina Liu; Wenjie Xin; Chenyang Li; Xingpeng Yin; Xuebo Xu; Feifei Bao; Zichun Hua (Elsevier, 2022)
Bacterial antitumor therapy has great application potential given its unique characteristics, including genetic manipulation, tumor targeting specificity and immune system modulation. However, the nonnegligible side effects and limited efficacy of clinical treatment limit their biomedical applications. Engineered bacteria for therapeutic applications ideally need to avoid their accumulation in normal organs and possess potent antitumor activity. Here, we show that macrophage-mediated tumor-targeted delivery of Salmonella typhimurium VNP20009 can effectively reduce the toxicity caused by administrating VNP20009 alone in a melanoma mouse model. This benefits from tumor-induced chemotaxis for macrophages combined with their slow release of loaded strains. Inspired by changes in the tumor microenvironment, including a decrease in intratumoral dysfunctional CD8+ T cells and an increase in PDL1 on the tumor cell surface, macrophages were loaded with the engineered strain VNP-PD1nb, which can express and secrete anti-PD1 nanoantibodies after they are released from macrophages. This novel triple-combined immunotherapy significantly inhibited melanoma tumors by reactivating the tumor microenvironment by increasing immune cell infiltration, inhibiting tumor cell proliferation, remodeling TAMs to an M1-like phenotype and prominently activating CD8+ T cells. These data suggest that novel combination immunotherapy is expected to be a breakthrough relative to single immunotherapy.